94.8k views
12 votes
Please help me answer this

Please help me answer this-example-1

1 Answer

7 votes

9514 1404 393

Answer:

z^11

Explanation:

The applicable rule of exponents is ...

(a^b)(a^c) = a^(b+c)

__


z^5\cdot z^6=z^(5+6)=\boxed{z^(11)}

__

Additional comment

It might help you to think of an exponent as indicating repeated multiplication. It tells you how many times the factor is repeated. In this case, it means ...


z^5\cdot z^6=(z\cdot z\cdot z\cdot z\cdot z)\cdot(z\cdot z\cdot z\cdot z\cdot z\cdot z)\\=z\cdot z\cdot z\cdot z\cdot z\cdot z\cdot z\cdot z\cdot z\cdot z\cdot z = z^(11)

User Ultraloveninja
by
5.7k points